Safety of milk‐derived bioactive peptides. (8th November 2016) - Beltrán‐Barrientos, Lilia María; García, Hugo S; Torres‐Llanez, María J; González‐Córdova, Aarón F; Hernández‐Mendoza, Adrián; Vallejo‐Cordoba, Belinda
Abstract : Bioactive milk peptides are protein fragments with potential biological activities. Over the past decades, studies have mainly focused on the health benefits of these bioactive peptides; however, only a few studies have evaluated their safety. In this review, we describe the scientific literature regarding their effects on both cell lines and on animal and human models, in terms of allergenicity, cytotoxicity, genotoxicity and mutagenicity.